Financial impact and adoption of solar irrigation in Rangpur, Bangladesh - Swati Anindita Sarker; Naiping Zhu; Fahad Almutlaq; K.M.Mehedi Adnan; Md Enamul Huq (Energy Strategy Reviews)
This study investigates the feasibility and socio-economic determinants of adopting solar-powered irrigation (SPI) systems in Bangladesh, focusing on their financial impact in boro rice production compared to diesel-powered irrigation (DPI). Sustainable irrigation technologies are critical for efficient agricultural land use, food security, and reducing environmental pollution in Bangladesh. SPI offers an innovative, eco-friendly alternative, but its adoption hinges on its financial benefits. Through a cost-benefit analysis, this research uncovers the superior gross returns, net returns, and benefit-cost ratios (BCR) of SPI users, with BCR values of 1.31 compared to 1.09 for DPI users. Data were collected from 404 farmers in two districts using a random sampling technique. A logit regression model identified 12 significant factors influencing SPI adoption, including educational status, monthly income, farming experience, extension contact, land and irrigation facility ownership, credit availability, soil fertility, perceptions of replacement costs, environmental awareness, and neighbor adoption. The study also highlights the inadequacy of Bangladesh's institutional framework for SPI technology development, suggesting the need for a bottom-up approach involving various governmental and non-governmental entities. This research provides critical insights for policymakers, advancing the understanding of renewable energy-based irrigation systems in the region.